Improving Mathematical Creative Thinking Ability In Creative Problem Solving Model With Scaffolding Strategy - Utari, Sindyeva Widya Hari; Dwijanto, Dwijanto; Dewi, Nuriana Rachmani (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The mathematical creativity of students in Indonesia is low. Students only imitate what the teacher does; if students are faced with a problem, they find it difficult to solve it. This study aims to determine the increase in students' mathematical creative thinking skills taught using the Creative Problem Solving model with a scaffolding strategy. The method used is pre-experimental, with one class serving as the experimental class for public junior high school 1 Batumarta VI students. The instrument in this study was a description of the test questions with the material on flat sides. The results of the study showed that there was a statistical increase in students' mathematical creative thinking abilities with the Creative Problem Solving model, which obtained an N-Gain value of 0,612 From this average value, 10 students were obtained in the high category and 16 students in the medium category and 3 students in low category